2017
DOI: 10.1111/hae.13182
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose factor VIII infusion in Chinese adult haemophilia A patients: pharmacokinetics evidence that daily infusion results in higher trough level than with every‐other‐day infusion with similar factor VIII consumption

Abstract: Our PK study shows low-dose factor VIII daily infusion results in higher trough level than with EOD infusion with similar factor VIII consumption in Chinese adult haemophilia A patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The substantial differences in PK profiles lead to FVIII dosing discrepancies compared with traditional fixed dosing regimens. 11,12,18,[23][24][25][26][27] The median t 1/2 observed in our study was similar to the half-life of Koate-DVI reported in the published data from Grifols (16.13 h). 28 The t 1/2 in our study would differ if a different concentrate was used.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The substantial differences in PK profiles lead to FVIII dosing discrepancies compared with traditional fixed dosing regimens. 11,12,18,[23][24][25][26][27] The median t 1/2 observed in our study was similar to the half-life of Koate-DVI reported in the published data from Grifols (16.13 h). 28 The t 1/2 in our study would differ if a different concentrate was used.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to those of other studies that evaluated the PK profiles of HA patients on prophylaxis with a standard regimen or LDP of FVIII. The substantial differences in PK profiles lead to FVIII dosing discrepancies compared with traditional fixed dosing regimens 11,12,18,23–27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that an FVIII level of 1% may still have more than five annual joint bleeds, while levels of 10%-12% or more have zero joint bleeds [29]. Studies have also shown that daily prophylaxis of 5 IU/kg achieved double the FVIII trough levels compared with 10 IU/kg every alternate day with same amount of factor consumption [30]. suggesting that there is a high heterogeneity among haemophilia patients [25].…”
Section: Studies With Personalized and Frequency Escalation Protocolsmentioning
confidence: 99%